KEPUASAN KERJA KARYAWAN DI HOTEL HOTEL ALIGA PADANG - Yulfiana, Dita; Yuliana, Yuliana; Suyuthie, Hijriyantomi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This study aims to determine the employee's satisfaction Aliga HotelPadang. This type of research is descriptive quantitative. Population of thisresearch is all employees Aliga Hotel Padang, amounting to 58 people. The sampleselection of this study using total sampling technique (58 people). Collecting datausing a questionnaire based on Likert Scale which has proven its validity andreliability. The results showed that overall job satisfaction of employees belong to acategory quite satisfied with the average value of 104.74 which were in the range of87.7 - <107.2. While based on individual indicators, namely: 1) The contents belongto the category of work is quite satisfied with an average of 18.84 in the range of15.7 - <19.2; 2) Supervision classified in categories quite satisfied with an averageof 19.19 in the range of 15.7 - <19.2; 3) Opportunity to advance classified incategories quite satisfied with an average of 18.24 in the range of 15.7 - <19.2; 4)Wages belong to the category quite satisfied with an average of 12.86 in the rangeof 11.2 - <13.7; 5) Co-workers belong to a category quite satisfied with an averageof 19.02 in the range of 15.7 - <19.2; 6) Working conditions are satisfied belong tothe category with an average 16.59 in the range of 16.5 - <19.5.